KONSEP PEMBIAYAAN DI BANK SYARIAH - Rahmawati Aprilia Astuti; Anggito Abimanyu; Farhat Diva Pangestu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Financing in Islamic banking represents the process of channeling funds to the public based on Islamicprinciples. This activity not only aims to generate financial returns but also emphasizes justice, transparency,and social responsibility. This article discusses the definition, function, legal foundation, and implementationprocess of financing in Islamic banking. Using a qualitative approach through literature studies fromvarious academic journals, the discussion reveals that Islamic financing fundamentally differs from conventional credit because it eliminates interest and replaces it with partnership-based schemes such asprofit-sharing, sale- based, or lease-based contracts. Islamic financing plays a vital role in promoting equitable economic growth through lawful and productive business activities that align with the values ofsharia